Application of the steady-state intestinal perfusion system in measuring intestinal fluid absorption and bicarbonate secretion in vivo - Fan, Wenjuan; Tan, Qinghai (Frontiers in Physiology, 2023)
Background: Steady-state intestinal perfusion system represents a tool in measuring intestinal fluid absorption and bicarbonate secretion in vivo, however, detailed procedures and parameters were not elucidated fully. Aim: We focused on the methods of steady-state intestinal perfusion system comprehensively including the blood pressure, hematocrit, blood gas and heart rate of mouse. Methods: Anesthetized, tracheally intubated and artificially ventilated mice were used for this system. Blood pressure, hematocrit, blood gas, heart rate as well as the rate of fluid absorption and HCO3- secretion at the different timepoint of small intestine and colon were evaluated. Results: Blood pressure, hematocrit, blood gas and heart rate got stable at 30min timepoint after surgery completion and could be kept for 2 hours. Rates of fluid absorption and bicarbonate secretion were also kept stable during the period of steady status of mice. Rates of fluid absorption and bicarbonate secretion were different among jejunum, ileum, proximal and mid-distal colon. Conclusion: Steady-state intestinal perfusion system is a reliable system for measuring intestinal fluid absorption and bicarbonate secretion in vivo.